Migrating Borders and Moving Times Temporality and the Crossing of Borders in Europe - Donnan, Hastings; Hurd, Madeleine; Leutloff-Grandits, Carolin (Rethinking Borders, 2016)
Migrating Borders and Moving Times analyses migrant border crossings in relation to their everyday experiences of time, and connects these to wider social and political structures. Sometimes border crossing takes no more than a moment; sometimes hours; some crossers find themselves in the limbo of detention; for others, the crossing lasts a lifetime to be interrupted only by death. Borders not only define separate spaces, but different temporalities. This book provides both a single interpretative frame and a novel approach to border crossing: an analysis of the reconfiguration of memory, personal and group time that follows the migrants' renegotiation of cross-border space and recalibrations of temporality.Using original field data from Israel and northern and south-eastern Europe, the contributors argue that new insights are generated by approaching border crossing as a process with diverse temporalities whose relationship to space has always to be empirically determined.